2009
DOI: 10.1007/s11515-009-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research of induced resistance to insects in cotton

Abstract: Any change in a plant that occurs following herbivory or environmental factors is an induced response. These changes include phytochemical induction, increases in physical defenses, emission of volatiles that attract predators and parasitoids of herbivores, and reduction in plant nutritional quality for herbivores, which is termed induced resistance. Induced resistance has been demonstrated ubiquitously in plants. It is one of our goals to review what is known about the induced resistance to herbivorous insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…Moreover, Villada et al, (2009) observed rapid accumulation of callose deposits, phenol, and lignin synthesis after aphid infestation on resistance melon type. In addition, our results showed that the tested insecticides significantly increased the leaf phenolic content, which may be because any change in a plant that occurs following herbivory or environmental factors is an induced response (Ti and Zhang 2009). Exposure of tobacco plants Nicotiana tabacum to soil application with Bensulfuron-methyl (BSM) herbicide increased jasmonic acid (JA) and SA concentrations and increased plant resistance to whiteflies (B. tabaci) and aphids (M. persicae) with the activation of resistance genes (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, Villada et al, (2009) observed rapid accumulation of callose deposits, phenol, and lignin synthesis after aphid infestation on resistance melon type. In addition, our results showed that the tested insecticides significantly increased the leaf phenolic content, which may be because any change in a plant that occurs following herbivory or environmental factors is an induced response (Ti and Zhang 2009). Exposure of tobacco plants Nicotiana tabacum to soil application with Bensulfuron-methyl (BSM) herbicide increased jasmonic acid (JA) and SA concentrations and increased plant resistance to whiteflies (B. tabaci) and aphids (M. persicae) with the activation of resistance genes (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…Cotton plants are rich in terpenoid compounds, which may function as a barrier against herbivores impairing growth/development and/or behavioral traits. However, the cotton plant has been modified during domestication and breeding for high yield and quality, including low gossypol oil in cottonseeds, which may have lessened the content of anti-herbivory secondary metabolites (such as gossypol) [36][37][38]. Information on secondary compounds in the cotton cultivars used in the present study was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton [ Gossypium hirsutum L. (Malvaceae)], a major host plant for H. armigera , is widely cultivated in China to the extent of around five million ha in 2011 (Zhu et al, ). This plant species has three categories of secondary metabolites, i.e., terpenoids, tannins, and flavones, that protect against herbivorous insects and other organisms (Ti & Zhang, ). The terpenoid gossypol, a typical plant allelochemical in Malvacea plants, is toxic to many lepidopteran larvae including H. armigera , Helicoverpa zea (Boddie), and Helicoverpa virescens (Fabricius) (Wang, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%